The impact of China’s green credit policy on green lending, green investment, and the environment - Li, Jiaqi (2024)
This thesis provides a comprehensive analysis of the effects of implementing green credit policy (GCP) in China on banks’ green lending, corporate green investment, and environmental pollution in China. China provides an ideal research setting as its huge economic growth presents a unique paradox, and China’s GCP presents its unique characteristics and the implementation of GCP in 2012 serves as an exogenous shock that allows us to isolate other contemporaneous factors. Drawing on institutional theory and data from 34 A- share listed Chinese banks from 2007 to 2020, the first study in Chapter 2 of this thesis demonstrates that GCP serves as an institutional mechanism, incentivizing banks to enhance their green lending. The results indicate that such implementation not only improves the financial performance of state-controlled banks but also contributes to a reduction in regional SO2 and CO2 emissions, thus confirming the positive externalities of banks’ enforcement of GCP. Relying on relationship banking theory, the second study in Chapter 3 shifts focus to the influence of local banks, represented by city commercial banks (CCBs), on corporate green investment. It reveals that in the wake of GCP, high- polluting firms (HPFs) in cities with local banks increased their green investment more than those without such banks. The impact is particularly significant for HPFs in regions characterized by stringent regulatory oversight, government involvement, and political connections, although a downturn in financial performance post-GCP implementation accompanies it. Based on Porter’s hypothesis, the third study in Chapter 4 employs a difference-in- difference (DID) approach using data from 284 cities over a six-year period to assess local banks’ impact on environmental pollution at the city-level. The findings indicate a marked decline in pollution levels in cities with local banks following GCP implementation, an effect magnified by the green credit extended by these banks. The research further elucidates that local banks facilitate pollution reduction by fostering innovation and decreasing local illiquidity, thereby suggesting that local banks are instrumental in directing financial resources toward environmentally sustainable outcomes. Together, this thesis proves that the implementation of GCP effectively advances China’s green economy and shapes a more sustainable future through the banking sector. This thesis also observes that GCP achieves environmental benefits at the cost of banks and firms’ profitability. Thus, the government needs to tailor GCP design to align economic interests with environmental interests, achieving full policy success. Finally, Chapter 5 concludes the whole paper and provides corresponding contributions, implications, limitations, and a future research idea with more details in the appendix.